2018
DOI: 10.1021/acs.jpcc.8b05885
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Density Functional Theory and Microkinetic Study to the Mn-Doped CeO2 Catalysts for CO Oxidation: A Case Study to Understand the Doping Metal Content

Abstract: CeO 2 doped with metal is employed in many catalytic reactions. Optimizing the content of metal is a routine step to improve the activity. In low doping metal content, the catalytic performance improves with the increase of the doping metal content. However, the catalytic performance decreases beyond the optimal doping metal content. To our best knowledge, the molecular level understanding to such phenomenon has never been reached. In the present study, Mndoped CeO 2 for CO oxidation has been taken as a case s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…A new CO oxidation mechanism. It was generally recognized that the reaction process of CO on the CeO 2 surface followed the M-vK mechanism, [47][48][49][50] that was, CO adsorbed on the CeO 2 surface and interacted with the lattice oxygen to form CO 2 . When CO 2 was desorbed, free O 2 molecules filled the oxygen vacancies.…”
Section: 32mentioning
confidence: 99%
“…A new CO oxidation mechanism. It was generally recognized that the reaction process of CO on the CeO 2 surface followed the M-vK mechanism, [47][48][49][50] that was, CO adsorbed on the CeO 2 surface and interacted with the lattice oxygen to form CO 2 . When CO 2 was desorbed, free O 2 molecules filled the oxygen vacancies.…”
Section: 32mentioning
confidence: 99%
“…Raman spectra together with XPS results claimed the presence of oxygen vacancies, which can be considered to be part of the active site for CO oxidation. [56,[75][76] Accordingly, the starting configuration was constructed by removing one O atom bonded with Cu from clean CeMnCuÀ M surface (Figure 9, state i, Supporting Information). Then, CO was firmly adsorbed on top of O v (O v -top) with adsorption energy of À 0.25 eV (Table S5).…”
Section: Eq Reactionmentioning
confidence: 99%
“…Co 2 MnO 4 exhibited a desirable effect in ethanol steam reforming (ESR) and postponed catalyst deactivation 22. It was found that Mn in a Ce‐Mn composite as a catalyst in various reactions played an important role in water dissociation and easier CO oxidation 23–25. A highly favorable influence of Mn on CuZn at low temperature in ESR was also proved 26.…”
Section: Introductionmentioning
confidence: 98%